2021
DOI: 10.1108/jhtt-09-2020-0243
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the pre-purchase experience through virtual reality. Insights from the cruise industry

Abstract: Purpose This study aims to provide an exploratory analysis of the role of virtual reality (VR) in the cruise context as a contribution to the limited literature on this topic. In particular, the research investigates immersive VR as a critical touchpoint at the pre-purchase stage of the customer journey. Design/methodology/approach To achieve the research aims, the authors use a case study approach by analysing the “immersive configurator” (essentially a virtual catalogue) implemented by the Mediterranean Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 61 publications
(89 reference statements)
0
9
0
Order By: Relevance
“…Third, VR is a powerful marketing tool for the tourism industry. Virtual tours can influence the intention to purchase and visit (Martínez-Molés et al , 2022; Simoni et al , 2022), as most tourists who use them tend to buy cruise vacations. This is because virtual tours allow them to try before buying, which helps in their decision-making process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, VR is a powerful marketing tool for the tourism industry. Virtual tours can influence the intention to purchase and visit (Martínez-Molés et al , 2022; Simoni et al , 2022), as most tourists who use them tend to buy cruise vacations. This is because virtual tours allow them to try before buying, which helps in their decision-making process.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis revealed that these behavioral outcomes (Martínez-Molés et al , 2022; Yung et al , 2021) are interconnected, with one leading to the other. For example, the intention to visit a cruise through virtual tours can lead to the intention to purchase a cruise vacation or recommend it to others (Simoni et al , 2022; Yang et al , 2021; Yung et al , 2021). Thus, passengers continue to use virtual tours even after the lifting restriction of the latest outbreak, recognizing they expedite services and enhance safety (Seyitoğlu and Ivanov, 2021).…”
Section: Framework For the Adoption Of Raisa In The Cruise Tourism Se...mentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest the host–guest relationship should be initiated through their avatars and all information usually exchanged before the arrival of guests, namely, requests for clarification or additional information, should take place in the most comfortable room of the prospective property, with the support of virtual reality. Insights from the cruise industry show an improvement of customer experience and interactivity in pre-purchase experience through the use of a virtual catalogue (Simoni et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Through the 360° virtual video, audiences can perceive a realistic representation of being in a place where they can get a “try before you go” experience. VR technology provides audiences with a pre-purchase journey (Simoni et al , 2022). Therefore, 360° virtual video is a powerful marketing tool for the tourism industry (Wu and Lai, 2021).…”
Section: Introductionmentioning
confidence: 99%